Edukasi Untuk Mencegah Penyakit Tuberculosis (TBC) Di Kalangan Masyarakat Banjarsengon Kecamatan Patrang, Jember, Jawa Timur - Riskha Dora Candra Dewi (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Tuberculosis (TB) is still a major global health problem and is spreading all over the world, including in Indonesia. In recent years, the incidence of TB in Indonesia has continued to increase. Data in East Java also shows that TB is increasing at any time and one of the largest is in Jember. This is caused by various factors, such as the lack of public knowledge about TB, high poverty rates, and lack of access to health services. Therefore, efforts are needed to increase public knowledge about TB and how to prevent its spread. The aim of this program is to provide education related to TB disease prevention among the people of Banjarsengon, Patrang District, Jember, East Java. The target of this program is the general public who are at risk of contracting TB, such as migrant workers, farmers and informal workers. The method used is presentation using actual references and socialization. Socialization can be done through various media, such as leaflets distributed to participants. The socialization material presented included an explanation of TB symptoms, ways of transmission, ways of prevention, and access to health services. Apart from that, educational media is also made, which can be in the form of short videos as an illustration for the participants of this education for prevention and early detection. With increasing public knowledge, it is hoped that it can reduce the incidence of TB among the community in Banjarsengon